“PHYSICAL EDUCATION AND RECREATION: DEVELOPERS OF MATHEMATICAL COMPETITION” (Fiep Bulletin - online, 2020)
The present research work, has the purpose of influencing favorably, so that both educational authorities, teachers in general, and especially those of physical education, we become aware of the importance of physical education, correlated with recreation, to be developers of the different skills that the student needs to use every day; and now specifically in the mathematical competence. Without a doubt, today it is important to look towards Physical Education, who, due to its unique and pedagogical nature, can potentially be considered, as a recreational and practical recreational instrument, to contribute to the development of mathematical competence. Mathematical competence develops the ability to use mathematical elements and reasoning, such as: numbers, measurements, geometric knowledge, as well as problems of probability and chance; in a school and extracurricular context (.http: //www.efdeportes.com/). In addition, Cajigal highlights the great intellectual component of our matter. While mathematics poses to children problems of mathematical logic that require a mental solution, Physical Education raises problems with motor problems, which require a mental solution, and at the same time require a motor solution. Isn't this a more enriching way of learning?
Keywords: Physical education; mathematics; recreation